(3HMhK h GhQGb Yeds ((3GdbGgQI(B:s (3efThQGJ GdefXeI GdYQHjI ddJfejI GdGOGQjI(B,s, 2009)
(3Jchjf hGYOGO GdbGOI , JCgjd h GYOGO GdbjGOGJ GdeGdjI h GdGOGQjI dehGLgIGdJMOjGJ GdeMdjI h GdOhdjI , Jchjf GdbjGOI GdGOGQjI I GdfeW GdbjGOj GdaYGd GdbjGOI JMJ GdVZhW JWhjQ h JMSjf GdegGQGJ GdbjGOjI ddGQGOGJ GdJfajPjI , GYOGO bjGOGJ GdUa GdGhd aj GdeLGdGJ GdGOGQjI h GdeGdjI , GdeOjQ GdYQHj GdeJejR , NUGFU h SeGJ GdeOjQ GdbGFO aj GdGdajI GdKGdKI h cjajI GYOGO GdeOjQ GdYQHj GdeJejR(B.s
Keywords: (3GdGOGQIs; (3GdGOGQI GdeGdjIs